(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background: It is expected that pharmacology education should prepare students as rational prescriber. Credibility of undergraduate pharmacology curricula is rather questionable in this aspect. As assessment shapes learning priorities, it is crucial to design assessment methods of pharmacology in right way to achieve the expected learning outcomes of future physicians. Materials and methods: This descriptive cross-sectional study was conducted to compare the reflection of curricular objectives, content coverage and national health priorities in undergraduate pharmacology written question papers (SAQ) of different universities of Bangladesh in last 10 years (January 2010 to November 2019). Total 131 question papers were collected, and reflection of curricular objectives, content coverage and selective disease burdens were evaluated and compared. Results: One objective regarding factual knowledge (Pharmacological effects, mechanisms of action, pharmacokinetic characteristics and adverse reactions of drugs) had significant higher weightage throughout the decade in all universities. There were statistically significant differences in weightage of reflection of five curricular objectives (p value <0.00001, 0.001, 0.003, 0.004, 0.02) among different universities. There was not a single question reflecting the ethical and legal issues involved in drug prescribing, development, manufacture and marketing in the decade in any university. Chemotherapy was the highest covered area (19.4±3.3), followed by central nervous system (1 6 . 0 ± 3 . 4 ) and general principles of pharmacology (14.3±3.2) throughout the last ten years in all universities. There was statistically also significant difference among different universities in weightage of all content areas except Gastrointestinal pharmacology. Statistically significant difference (p value < 0 . 0 0 0 0 1 ) among different universities in cardiovascular diseases burden was observed. Conclusion: Current study found variation in pharmacology written question papers of different universities in the aspects of reflection of curricular objectives, content coverage and cardiovascular disease burden. Chatt Maa Shi Hosp Med Coll J; Vol.21 (2); July 2022; Page 3-8